Role of Nanotechnology in Prosthodontics: a review - Sreenivasulu, Duggineni; Reddy, N Simhachalam; Sowjanya, J Lakshmi (International Journal of Dental Materials, 2023)
In the present-day context, a considerable portion of the population faces the challenge of edentulism. Various treatment approaches, including both fixed and removable prostheses, are available for restoring missing teeth. Noteworthy progress has recently been observed in the characteristics of commonly used dental materials, attributed to the emergence of nanotechnology. This technological advancement has significantly contributed to improving the outcomes of dental treatments. Nanotechnology represents a multidisciplinary domain that amalgamates principles from both the arts and sciences, involving the manipulation of structures and functional materials at a minuscule scale. This field leverages various physical and chemical methodologies to operate at dimensions where sizes of particles, typically ranging from 1 to 100 nanometers, give rise to what is termed as Nanoparticles. The integration of nanoparticles in dentistry, particularly within dental materials such as ceramics, acrylic resin, tissue conditioners, and denture adhesives, has exhibited a discernible positive impact on their inherent properties. This review predominantly delves into an exploration of diverse applications of nanoparticles within the realm of dentistry, with a specific emphasis on their role in prosthodontics.